PENGARUH PROFITABILITAS, STRUKTUR AKTIVA DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL (STUDI EMPIRIS PADA PERUSAHAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2017) - Fauziyatul Uffah; Ronny Malavia Mardani; M. Agus Salim (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT The purpose of this study was to empirically examine the effect of profitability, asset structure and firm size on the capital structure of the food and beverage sub-sector manufacturing companies listed on the Indonesia stock exchange for the period 2015-2017. The sample in the study used a purposive sampling method. based on existing criteria obtained 46 companies that became the study sample. The technical data analysis used in this study is multiple linear analysis. The results of the study show that the profitability variable has a negative and significant effect on the capital structure, the asset structure does not affect the capital structure and the size of the company does not affect the capital structure.keywords: profitability, asset structure, company size, capital structure